IMPLEMENTASI PENDIDIKAN AGAMA ISLAM PADA MATERI AKIDAH AKHLAQ DALAM MEMBENTUK KARAKTER SISWA KELAS X DI SMA 45 PURWODADI PASURUAN - Mohammad Aufa Khilmi; Muhammada; Saifulah; Muhammad Nur Had (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of Islamic Religious Education (PAI), especially the Aqidah Akhlaq material, in shaping the character of polite students in the school environment. However, technological developments, the influence of social media, and the lack of family supervision pose challenges in shaping students' character. This study aims to describe the implementation of Islamic Religious Education on the Aqidah Akhlaq material in shaping the character of polite students of grade X at SMA 45 Purwodadi, Pasuruan, and identify supporting factors, inhibiting factors, and efforts made to overcome them. This study uses a qualitative approach with a descriptive case study method. Data were obtained through observation, interviews, and documentation, then analyzed descriptively. The results show that the implementation of Aqidah Akhlaq learning is carried out through habituation of religious activities, teacher role models, and interactive learning. This program has a positive impact on student behavior, such as increasing respect for teachers, habits of greeting, being mindful of speech, and respecting the opinions of friends. Supporting factors include a religious school environment, the support of the principal, and parental cooperation, while inhibiting factors include the influence of social media and lack of family supervision. Overall, learning Akidah Akhlaq has proven effective in forming students' polite character.